PERUBAHAN SIKAP AKSEPTOR SEBELUM DAN SESUDAH KONSELING TENTANG PEMERIKSAAN ULANG PASCA PEMASANGAN IUD DI DESA MANGARAN KECAMATAN AJUNG TAHUN 2011 - Ratna Suparwati; Lulut Sasmito; M Misiyem (Fakultas Kesehatan Masyarakat, Universitas Jember, 2013)
The results BKKBN Center (2010) found that the acceptor inspection afterinstallation of the IUD and some of them do not exercise control on the groundsthere was no suggestion from the officer, did not know and no complaints. Thereason is because the officer did not provide full counseling about the IUD andside effects that may arise after the installation, or due to lack of staff knowledgeabout these devices that cause they do not provide complete and correctinformation. One way to handle it is by counseling. Counseling is an attempt to help resolve conflicts, obstacles and difficulties inmeeting our needs, as well as efforts to improve mental health. This study aims to identify changes in attitude acceptors before and aftercounseling on post-installation re-examination of the IUD. The study design was a one group pre test – post test, the population of IUD acceptors in the working area Ajung Village Health Center in 2011 Mangaran some 54 people with a sample ofsome 47 people. The number of samples that do not meet the criteria of thesample as many as 7 people, so the number of samples that meet the criteria of the sample as many as 40 people. Data were collected with questionnairs measuringinstruments covered by using Likert scale before and after counseling. Results of research prior to counseling 18 acceptors (45%) had a positive attitudeand 22 acceptors (55%) having a negative attitude. After counseling obtained 25acceptors (62,5%) ang 15 acceptors (37,5%) having a negative attitude. Statistical test Wilcoxon Match Pairs Test = 5,513. Because the count Z > Z table(5,513>1,96), so that Ho refused. This means that there is a change in attitudeacceptors before and after counseling on post-installation re-examination of theIUD. Therefore, counseling should be done continuously to increase thepercentage of acceptors who perform post-installation re-visit the IUD.